The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1952
DOI: 10.1084/jem.95.5.429
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Adjuvants in Studies on Influenza Immunization

Abstract: Rather early in studies on influenza immunization in animals as well as in man, it was realized that immunizing effect, as reflected in antibody response induced by the vaccines employed, was limited and of relatively short duration. For these reasons (1) a variety of methods were explored for enhancing and prolonging the protective effect induced by vaccination (2-7). None, however, provided such striking results as those obtained in studies in animals reported by Friedewald (6), and in studies in man reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1953
1953
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(12 citation statements)
references
References 12 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…Immunization procedure. The antigens used were incorporated in a water in oil-adjuvant mixture, according to Salk & Laurent (1952). Ten parts of 5% gelatin-derivative solution, 1 part of Arlacel A (Atlas Powder Co., Wilmington, Del., U.S.A.) and 9 parts of Bayol F (Stanco Distributors, New York, U.S.A.) were homogenized by repeated filling and forcible ejection from a syringe.…”
Section: Methodsmentioning
confidence: 99%
“…Immunization procedure. The antigens used were incorporated in a water in oil-adjuvant mixture, according to Salk & Laurent (1952). Ten parts of 5% gelatin-derivative solution, 1 part of Arlacel A (Atlas Powder Co., Wilmington, Del., U.S.A.) and 9 parts of Bayol F (Stanco Distributors, New York, U.S.A.) were homogenized by repeated filling and forcible ejection from a syringe.…”
Section: Methodsmentioning
confidence: 99%
“…Muramyl dipeptide expressed by MTb in CFA activates NOD2 receptors [67,68]. Incomplete Freund’s adjuvant (IFA) composed of just the mineral oil component of CFA, was used in influenza vaccines in the 1950s to enhance antibody responses [69], and due to significant side effects [70] has only been studied in clinical trials of HIV and some cancer vaccines [71]. It enhances accumulation of APCs, antigen uptake and cytokine production and a non-polarized TH1/TH2 response with enhanced IgG1/IgG2a antibody responses [7276].…”
Section: Emulsion Based Adjuvantsmentioning
confidence: 99%
“…However, the failure of the same vaccine to have any impact on the 1947 epidemic led both to the recognition of antigenic variation, implying that new vaccines would be needed each flu season, and to efforts to increase vaccine potency. In the first study of influenza vaccines employing NHPs, Jonas Salk and his colleagues reported in 1951 and 1952 that the standard vaccine prepared in a water-in-oil emulsion and delivered intramuscularly to rhesus macaques elicited a much stronger antibody response than the vaccine without adjuvant (Salk and Laurent, 1952;Salk et al, 1951) (Table S6). The animals were not subsequently challenged with influenza virus.…”
Section: Experimental Infections Of Nhps With Human Influenza VImentioning
confidence: 99%